Disruption of cellular iron homeostasis by IREB2 missense variants causes severe neurodevelopmental delay, dystonia and seizures. Issue 3 (19th April 2022) - Maio, Nunziata; Saneto, Russell P.; Steet, Richard; Sotero de Menezes, Marcio A.; Skinner, Cindy; Rouault, Tracey A.
Abstract: Altered brain iron homeostasis can contribute to neurodegeneration by interfering with the delivery of the iron needed to support key cellular processes, including mitochondrial respiration, synthesis of myelin and essential neurotransmitters. Intracellular iron homeostasis in mammals is maintained by two homologous ubiquitously expressed iron-responsive element-binding proteins (IRP1 and IRP2). Using exome sequencing, two patients with severe neurodegenerative disease and bi-allelic mutations in the gene IREB2 were first identified and clinically characterized in 2019. Here, we report the case of a 7-year-old male patient with compound heterozygous missense variants in IREB2, whose neurological features resembled those of the two previously reported IRP2-deficient patients, including a profound global neurodevelopmental delay and dystonia. Biochemical characterization of a lymphoblast cell line derived from the patient revealed functional iron deficiency, altered post-transcriptional regulation of iron metabolism genes and mitochondrial dysfunction. The iron metabolism abnormalities of the patient cell line were reversed by lentiviral-mediated restoration of IREB2 expression. These results, in addition to confirming the essential role of IRP2 in the regulation of iron metabolism in humans, expand the scope of the known IRP2-related neurodegenerative disorders and underscore that IREB2 pathological variants may impact the iron-responsive element-binding activity of IRP2 with varying degrees of severity. The three severely affected patients identified so far all suffered from complete loss of function of IRP2, raising the possibility that individuals with significant but incomplete loss of IRP2 function may develop less severe forms of the disease, analogous to other human conditions that present with a wide range of phenotypic manifestations. Abstract : Maio et al. report a patient with IREB2 missense variants and neurological features resembling those of two previously described patients . This study reinforces IREB2 importance in iron metabolism regulation in the central nervous system and confirms that IREB2 mutations cause a newly characterized type of early onset progressive neurodegenerative disease. Graphical Abstract: Graphical Abstract